(untitled) (Memorias Sifored - Encuentros Educación UAN, 2022)
This research was developed from the reflection of our what to do as teachers punctually in the Restrepo Millán district school located in the Rafael Uribe Uribe locality of the city of Bogotá, with the population of tenth grade students belonging to the deepening of Design. It has been shown that students present various difficulties with the spatial geometric thinking competence, which focuses on the appropriation of concepts and geometric figures applied to the creation of compound designs. In inquiring about this type of thinking, Hoffer and Van Hiele have developed two theories that contribute to the understanding of geometry respectively. Hence, a diagnostic instrument was formulated that obeys the understanding skills of Hoffer’s geometry and the teaching levels of van Hiele’s geometry; in order to identify geometric concepts, geometric transformations and creation of flat compound designs, and thus determine the level of development of thought in the study population.